2015
DOI: 10.1108/ijem-10-2013-0150
|View full text |Cite
|
Sign up to set email alerts
|

University choice: what do we know, what don’t we know and what do we still need to find out?

Abstract: University choice: what do we know, what don't we know and what do we still need to find out? Jane Hemsley-Brown Izhar Oplatka Article information: To cite this document: Jane Hemsley-Brown Izhar Oplatka , (2015),"University choice: what do we know, what don't we know and what do we still need to find out?" AbstractPurpose -The purpose of this paper is to systematically document, scrutinise and critically analyse the current research literature on higher education choice to: establish the scope of the studies;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 93 publications
5
103
1
8
Order By: Relevance
“…As also stated in the aforementioned research by Hemsley-Brown and Oplatka (2015), geography is a driver for University election, but it remains unclear, out of our results, if International Master students really look for proximity, or the geographical issue concerns more a search of diversity and novelty. Cultural distance has also underpinning in this evaluation, as some participants in Group A were Latin-American studying in Spain, a country geographically very distant, but culturally (language, religion) close.…”
Section: The Get-dimensions -Benefitsmentioning
confidence: 50%
See 2 more Smart Citations
“…As also stated in the aforementioned research by Hemsley-Brown and Oplatka (2015), geography is a driver for University election, but it remains unclear, out of our results, if International Master students really look for proximity, or the geographical issue concerns more a search of diversity and novelty. Cultural distance has also underpinning in this evaluation, as some participants in Group A were Latin-American studying in Spain, a country geographically very distant, but culturally (language, religion) close.…”
Section: The Get-dimensions -Benefitsmentioning
confidence: 50%
“…As aforementioned, except for one case, students in each focus group came from the same University (see Table 1); the homogeneity in finding University image as a driver is not surprising, according to previous literature (Hemsley-Brown & Oplatka, 2015). As a matter of example, It was told in focus group A that the students viewed their institution as "one of the top ones among the others in Spain".…”
Section: The Get-dimensions -Benefitsmentioning
confidence: 73%
See 1 more Smart Citation
“…Davies et al (2013) surveyed nearly 1400 school leavers and report that males and certain ethnic groups were more likely to justify going to university on labour market and income grounds, but that they and other groups also cited additional factors such as job status, creativity, and altruism as driving their decision to study. HemsleyBrown and Oplatka (2015) systematically reviewed the English language literature on university selection and found over 40 'choice factors', of which only a handful would be considered employment or financially oriented. Two further studies (Jary and Shah 2009;Mann 2010) incorporated interviews in their studies and again found students citing altruistic, intrinsic rationales for studying alongside instrumental ones.…”
Section: Instrumentalismmentioning
confidence: 99%
“…Student choice is becoming an important factor in determining the sustainability of the sector (Briggs 2006). Global financial constraints have forced universities to investigate different methods and modes to increase student enrolment (Hemsley-Brown & Oplatka 2015).…”
Section: Introductionmentioning
confidence: 99%